Jabatan Kepala Sekolah; Antara Jabatan Administrasi Atau Jabatan Politik - Kurniawan, Ade (Al Mabhats : Jurnal Penelitian Sosial Agama, 2019)
The principal's position is the highest administrative office in the school. The principal has an important role in coordinating, mobilizing and harmonizing all available educational resources in the school in order to realize the school's vision, mission, goals and objectives through programs that are implemented in a planned and gradual manner. To produce a professional headmaster, the recruitment process is an important stage that must be carried out professionally, transparently and accountably. The stages that must be carried out in the recruitment of principals are: (a) nomination of candidates by the principal / madrasah and / or supervisor of the school / madrasah, (b) administrative selection, (c) academic selection. But in the process in the field, the recruitment stage is often ignored and almost not carried out and even strongly suspected by political interests.